Subcostal Transversus Abdominis Plane Block for Laparoscopic Sleeve Gastrectomy, Is It Worth the Time? - CİNGİ, ASIM; ARSLANTAŞ, MUSTAFA KEMAL; UPRAK, TEVFİK KIVILCIM (SPRINGER, 2019)
BackgroundObesity is a complex and multifactorial disease whose incidence has increased, making it a serious public health issue. Laparoscopic sleeve gastrectomy (LSG) is one of the most common surgical procedures that is chosen for bariatric surgery. Decreasing postoperative pain in these patients which will increase patients' compliance and quality of life will lead to better surgical results. This study aims to compare the effectiveness of trocar site infiltration versus bilateral subcostal transversus abdominis plane block (TAP) in controlling postoperative pain in patients.MethodsForty-five consecutive patients who have undergone LSG in xxx General Surgery Department have been enrolled in the study. Patients were divided into two groups according to the surgeon's choice. The first group underwent TAP block, while the second group underwent trocar site infiltration. Patients' pain was recorded via visual analogue scale (VAS) in postoperative periods.ResultsTwenty-nine female (69%) and 13 (31%) male patients were included in the study. Median age was 41 (18-58) and median BMI was 48 (41.1-68). When the VAS values were compared, in the TAPB group, 6th hour resting and coughing pain was statistically significantly less. Other VAS values measured while resting, coughing, and post-mobilization did not show significant differences. There were no significant differences between the groups' tramadol use.ConclusionsAfter LSG, TAP block and trocar site infiltration yield similar pain control. Due to the faster application and fewer side effects, we concluded that trocar site infiltration should be the intervention of choice in controlling postoperative pain in LSG.
Keywords: Bariatric surgery; Obesity; Postoperative pain; TAP block; LSG; BARIATRIC SURGERY; ANALGESIC EFFICACY; DOUBLE-BLIND; CHOLECYSTECTOMY; GUIDELINES; PAIN